UNCONVENTIONAL MARKETING STRATEGIES AND TACTICS - Ristevska jovanovska, Snezhana (INSTITUTE OF KNOWLEDGE MANAGEMENT SKOPJE, MACEDONIA, 2018)
The primary idea behind IMC strategy is to create a seamless experience for consumers across different aspects of the marketing mix. Since marketers are always looking for more ways to get to their potential target markets, guerrilla marketing itself has become an umbrella term for even more specific communication strategies designed to engage and surprise the consumer with their products and services. Viral marketing describes any strategy that encourages individuals to pass on a marketing message to others, creating the potential for exponential growth in the message’s exposure and influence. Some viral marketing strategies work better than others. The basic elements you hope to include in your viral marketing strategy need not conta-in all these elements, but the more elements it embraces, the more powerful the results are likely to be: gives away valuable products or services, provides for effortless transfer to others; scales easily from small to very large; exploits common motivations and behaviors; utilizes existing communication networks; takes advantage of others’ resources. Guerrilla marketing behavior delivers publicity via local unconventional marketing activity that makes people sit up and notice think “shock and awe”. Promotion is one of the marketing mix elements among a system of five in a promotional plan. These elements are personal selling, advertising, sales promotion, direct marketing, and publicity. A promotional mix specifies how much attention to pay to each of the five subcategories, and how much money to budget for each. There are different ways to promote a product in different areas of media. Promoters use Internet advertisement, special events, endorsements, and newspapers or magazines to advertise their product. Many times with the purchase of a product there are incentives like discounts, free items, or contests. The aim of the research in this paper is to determine the impact of viral and guerrilla strategies to the customers decision making process when buy some cosmetics products. The survey was conducted on a random sample of highly educated respondents, active and intensive Internet users and social networks. According to the received results the facts in hypotheses: (1) Invonvencional forms of marketing (viral and guerrilla marketing) has a bigger impact on the customers decision making process to buy products for sport activities than advertisements on television and radio - is confirmed; (2) Viral campaigns, as a form of promotional activity has a bigger impact than guerrilla marketing on the customers decision making process to buy products for sport activities - is confirmed. According to received results viral marketing is better than guerrilla marketing for first, second and fifth statement for another statement (third, fourth, six and seven) guerrilla score is better than the score for viral marketing.